Neural basis of social learning, social deciding, and other-regarding preferences - Steve W. C. Chang (Frontiers Research Topics, 2015)
Humans and many other social animals decide, or learn when necessary, what to do in a given social situation by assessing a range of variables related to social states (e.g., competitive or cooperative), others' overt behavior (e.g., response choices and outcomes), others' covert mental states (e.g., beliefs, intentions and desires), and one's own interpersonal inclination (e.g. other-regarding preferences and generosity). Recent studies in social neuroscience have begun to uncover how such social variables are processed, encoded, and integrated in the brain. The goal of the current Research Topic is to promote a better understanding of neural basis of social learning, social decision-making, and other-regarding preferences.